Similarities and Differences in Fish Community Composition Accessed by Electrofishing, Gill Netting, Seining, Trawling, and Water eDNA Metabarcoding in Temperate Reservoirs - Golpour, Amin; Šmejkal, Marek; Čech, Martin; dos Santos, Rômulo A.; Souza, Allan T.; Jůza, Tomáš; Martínez, Carlos; Bartoň, Daniel; Vašek, Mojmír; Draštík, Vladislav; Kolařík, Tomáš; Kočvara, Luboš; et al. (Frontiers in Ecology and Evolution, 2022)
It is difficult to understand the composition and diversity of biological communities in complex and heterogeneous environments using traditional sampling methods. Recently, developments in environmental DNA metabarcoding have emerged as a powerful, non-invasive method for comprehensive community characterization and biodiversity monitoring in different types of aquatic ecosystems. In this study, water eDNA targeting fish (wf-eDNA) and four traditional fish sampling methods (electrofishing, gill netting, seining, trawling) were compared to evaluate the reliability and efficiency of wf-eDNA (vertebrate mitochondrial 12S ribosomal RNA (rRNA) as an alternative approach to assess the diversity and composition of freshwater fish communities. The results of wf-eDNA showed a consistency between the traditional sampling methods regarding species detection. However, some fish species detected using wf-eDNA assay were not detected using traditional sampling methods and vice versa. Comparison of wf-eDNA and traditional sampling methods revealed spatial homogeneity in fish community composition in all reservoirs. Ordination analysis showed that the wf-eDNA approach covers all traditional sampling methods and occupies an intermediate position. In addition, based on the Shannon diversity index, we found that in one reservoir the wf-eDNA method yielded similar fish community diversity to traditional sampling methods. However, in other reservoirs, the calculated Shannon diversity index of the wf-eDNA method was significantly higher than traditional sampling methods. In general, significant positive correlations were found between the wf-eDNA method and almost all traditional sampling methods. We conclude that wf-eDNA seems to be a reliable and complementary approach for biomonitoring and ecosystem management of freshwater ichthyofauna.